Renin–angiotensin system blockers, risk of SARS-CoV-2 infection and outcomes from CoViD-19: systematic review and meta-analysis. Issue 2 (31st December 2020) - Lee, Matthew M Y; Docherty, Kieran F; Sattar, Naveed; Mehta, Neil; Kalra, Ankur; Nowacki, Amy S; Solomon, Scott D; Vaduganathan, Muthiah; Petrie, Mark C; Jhund, Pardeep S; McMurray, John J V
Abstract: Aims: This meta-analysis provides summary odds ratio (OR) estimates for associations between treatment with (vs. without) renin–angiotensin system blockers and risk of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection and coronavirus disease 2019 (CoViD-19) severity (including case-fatality) in patients with hypertension, and in all patients (irrespective of hypertension). Methods and results: PubMed, EMBASE, Web of Science, Google Scholar, medRxiv, and SSRN were searched (2 May 2020 to 12 August 2020) for non-randomized observational CoViD-19 studies. Event/patient numbers were extracted, comparing angiotensin-converting enzyme (ACE) inhibitor/angiotensin-receptor blocker (ARB) treatment (and each separately), to treatment with neither drug, for the outcomes: (i) likelihood of SARS-CoV-2 infection; (ii) CoViD-19 severity [including hospitalization, intensive therapy unit (ITU), ventilation]; (iii) case-fatality. The risk of bias was assessed (ROBINS-I). Random-effects meta-analysis estimates were pooled. Eighty-six studies including 459 755 patients (103 317 with hypertension), were analysed. In patients with hypertension, ACE inhibitor or ARB treatment was not associated with a greater likelihood of SARS-CoV-2 infection in 60 141 patients (OR 1.06, 95% CI 0.99–1.14), hospitalization in 5925 patients (OR 0.90, 0.62–1.31), ITU in 7218 patients (OR 1.06, 0.73–1.56), ventilation (or ITU/ventilation/death) in 13 163 patients (OR 0.91, 0.72–1.15) or case-fatality in 18 735 patients with 2893 deaths (OR 0.75, 0.61–0.92). Conclusion: Angiotensin-converting enzyme inhibitors and ARBs appear safe in the context of SARS-CoV-2 infection and should not be discontinued. PROSPERO registration number CRD42020186996.